Pengaruh Suplemen Katalitik terhadap Karakteristik dan Populasi Mikroba Rumen Domba - H T Uhi; A Parakkasi; B Haryanto (Faculty of Animal Science, Bogor Agricultural University, 2006)
Dry season resulted in lower availability of ruminant feeds with subsequent effects on reduction of sheep productivity; therefore nutritive supplement may be required. The objective of this experiment was to study the effect of supplementation of catalytic substrate consisting of gelatinized sago, ammonium sulfate, Co and Zn on the sheep rumen characteristics and its microbial population. Forty lambs with an average live weight of 13 kg were divided into 8 blocks to test 5 feeding treatments. The treatments were feeding low quality forage without supplement (R1), R1 plus catalytic supplement at 10% of ration (R2), 20% (R3), 30% (R4) and a positive control treatment (R0 = R1 + soybean meal). Parameter measurements included rumen pH, ammonia, VFA and microbial population. It was observed that the rumen pH ranging from 6,06 (R1), 6,15 (R2), 6,45 (R4), 6,58 (R3) and 6,85 (R0). The rumen concentrations of ammonia were 5,83 mM (R3), 6,01 mM (R4), 6,35 mM (R2), 8,30 mM (R0) and 9,36 mM (R1) with total volatile fatty acid concentration ranging from 154, 88 mM (R1), 163,70 mM (R2), 180,89 mM (R0), 188,79 mM (R4) and 194,71 mM (R3). Population of rumen bacteri for R3 was 6,09 x 109 cell/ml, which was greater than RO (5,57 x 109 cell/ml), R1 (4,36 x 109 cell/ml), R2 (4,15 x 109 cell/ml), R4 (5,60 x 109 cell/ml), while protozoa R3 (2,59 x 106 cell/ml), was lower than RO (3,51 x 106 cell/ml) R1 (5,49 x 106 cell/ml) R2 (5,61 x 106 cell/ml) R4 (3,31 x 106 cell/ml). Catalytic supplement at 20% of ration (R3) resulted in a normal rumen concentration of ammonia and pH, and increased VFA concentration. It was concluded that catalytic supplement at 20% of ration was the appropriate level for optimal rumen characteristics.Key words : catalytic supplement, minerals, microbes, rumen, sheep